CO2 monitoring associated with the quality of soybean grains stored in different moisture contentes - SOUZA, Diene Gonçalves; RESENDE, Osvaldo; ZUCHI, Jacson; FERREIRA, Paulo Victor Alcântara; MABASSO, Geraldo Acácio (Food Science and Technology, 2023)
The objective of this study was to quantify the levels of CO2 produced by soybeans stored at room temperature in a prototype silo, with initial moisture contents of 12, 14, and 16% (w.b.), as well as to evaluate the quality of the product over storage. Analyses of the moisture content, ash, proteins, lipids, color, germination, and electrical conductivity were performed. In the atmosphere in the silos, the amount of CO2, relative humidity, and temperature were monitored every hour using a CO2 meter data logger. Grain quality evaluations took place at four storage times (0, 30, 60, and 90 days). Analyses were performed in triplicate, and data were analyzed using analysis of variance and regression, adopting the 5% level of significance. The moisture contents, protein, lipids, germination, and color were reduced over time, resulting in a loss of grain quality. Soybeans initially stored with 16% (w.b.) of initial moisture content showed greater losses associated with the rise in the levels of CO2. The rise in CO2 emission in the internal atmosphere of the silo signals the beginning of grain deterioration and can be used as a decision-making tool, aiming at preventing and reducing losses in product quality over storage.